상상력에 기반한 융합 현대음악에 대한 분석과 적용 - 자연배음에서 파생되는 음 소재들을 중심으로 - 박이제 (교양교육연구, 9(2), 2015)
이 글의 목적은 <피아노 5중주를 위한 “Werden und Vergehen”>의제1악장에서 사용된 융합 현대음악(Fusion-Contemporary Music)의 음 소재들을 파악하여 거시적인 동시에 미시적인 분석에 있다. 이 연구에서는 전체 3악장 가운데 제1악장을 중심으로 한 분석이다. 특히 상상력으로부터 비롯된 융합 현대음악인 “생성과 소멸” 즉, “Werden und Vergehen”의 구조적인 특징과 다양성의 제시는 다른 연구와 비교할 때 차별성을 내포하고 있다. 이는 자연배음(Overtone)에서 파생되는 서양적이며 한국적인 여러 가지 음 소재를 파악하여 분석적으로 제시할 뿐만 아니라, 자연배음과 하행(Under Tone), 신비적이며 창의적인 에너지와 인간의 의지력 등이 반영되어 표출된다. 이를 위해 제1악장의 분석적 핵심내용은 도표를 통해 제시되며, 한국의 전통음악 선율과 서양음악의 자연배음에서 파생된 서양의 소재들에 대해 상호 비교하여 분석한다. 또한 제1악장의 형식, 음 소재, 동기와 주제, 변화, 발전, 상징어와 대비, 악기연구, 융합구조의 특징, 시김새 등에 대해 객관적으로 분석한다. 그리고 제1악장의 5개의 부분은 참고악보를 통해 미시적으로 분석하여 설명하며, 구조적 특징에 대해서도 제시한다. 이러한 분석적 내용을 포함하고 있는 본 논문에서는 융합 현대음악의 교육효과를 극대화하기 위해 효율적인 지도방안이 제시되며, 다차원적인 창작사고에 의해 결합되어 있는 구조적 특징이 분석을 통해 제시된다. 끝으로 본 논문은 자연배음에서 파생된 동서양의 음 소재를 융합한 현대음악의 발전에 기틀을 마련할 뿐만 아니라 “현대음악의 이해”라는 교양과목에도 활용할 수 있다는 점에서 그 의미를 찾을 수 있을 것이다. The goal of our paper is analyzing tones of fusion-contemporary music which is used in the 1st movement of <“Werden und Vergehen” for Piano Quintet> in terms of both macroscopic and microscopic view. In this research our prime concern is the 1st movement among whole three movements. Comparing with other research, especially, it can be distinguished by analyzing structural feature and suggesting diversity of “Werden und Vergehen”.(one of the Fusion-Contemporary Music started by imagine.) Various both Western and oriental tones derived from Overtune are analyzed. And this analysis are expressed by an up-downward of Overtune, mystical and creative energy, will power of human. The analytical key point of 1st movement is shown by charts. Furthermore, the Korean traditional melodies and subject matters derived from overtone of western music are compared each other. In addition, Musical Form, Tone Sources, Theme, Motive, Change & Development, Symbolic Language & Contrast, Researching Instrument, Features of Fusion System, Sigimse of 1st movement are analyzed objectively. Five parts of 1st movement are described with reference, and structural features are also presented. In this paper including various analytical point of view, not only efficient guidance plan for amplifying Fusion-Contemporary Music education effect but also structural feature, combination of multidimensional creative thoughts, are suggested. Finally, this research is remarkable in terms of showing both bridge effect and possibility of improving creative modern music by fusion of oriental, western subject matters. KCI Citation Count: 0